The first step for understanding the molecular mechanism of the antifibrotic effect of inhaling 25(OH)-vitamin D3 and 1,25(OH)2-vitamin D3 in the murine model of hypersensitivity pneumonitis - Lemieszek, Marta Kinga; Chojnacki, Michał; Paśnik, Iwona; Wilczyńska, Alicja; Gawryś, Wiktoria; Anisiewicz, Jakub; Leśniowska, Ilona; Kiełbus, Michał (Frontiers in Pharmacology, 2025)
IntroductionPulmonary fibrosis occurs in several respiratory diseases, among which hypersensitivity pneumonitis (HP) is often ignored in designing therapeutic strategies. We strive to fill these knowledge gaps. Our earlier studies revealed antifibrotic potential of the inhalation of 1,25(OH)2-VD3 and 25(OH)-VD3 based on modulation of the immune response and deposition of extracellular matrix components, both of which are important components of epithelial–mesenchymal transition (EMT), which we focused on in this research. The study aimed to describe the direct impact of VD3-metabolites on EMT in the course of pulmonary fibrosis in HP to understand their therapeutic effect.MethodsThe research was performed in the HP model, wherein pulmonary fibrosis is induced in mice by chronic exposure to antigens of Pantoea agglomerans (SE-PA). The study was conducted in VD3-deficient mice, while VD3-sufficient mice were used as the main control. VD3-deficient mice inhaled 100 pg/g of 25(OH)-VD3 or 5 pg/g of 1,25,25(OH)2-VD3 used separately or with SE-PA for 14 days and 28 days. The range of pulmonary fibrosis was determined after Masson trichrome staining. Expression of EMT molecules was examined using real-time PCR and Western blot.Results and discussionThe studies revealed that VD3-deficiency triggers EMT, the signs of which were increased expression of EMT transcription factors (Snail1, Snail2, Zeb1, and Zeb2), inhibited expression of epithelial cell markers (E-cadherin and occludin), and altered expression of mesenchymal cell markers, including upregulated N-cadherin and vimentin. Pathological changes caused by VD3-deficiencies accelerated in response to SE-PA, the signs of which were: 1) upregulated expression of Snail1, Snail2, Zeb1, Zeb2, Acta2, Cdh2, Fn1, and Vim; 2) downregulated expression of Cdh1 and Ocln; 3) increased level of α-SMA, fibronectin, vimentin, and occludin; 4) decreased amount of N-cadherin; 5) increased deposition of fibers in lung tissue. All negative changes recorded on the transcriptome level in VD3-deficient mice with HP were effectively reduced by inhalations of 25(OH)-VD3 and 1,25,25(OH)2-VD3, suggesting that their antifibrotic effects are associated with EMT inhibition. Nevertheless, the beneficial impact of VD3-metabolites on the proteome level was associated with restoration of the balance in the expression of EMT molecules disturbed by cholecalciferol deficiency and SE-PA exposure; metabolites lowered the overexpressed amounts of fibronectin, vimentin, and occludin and simultaneously increased the expression of vitamin D3 metabolites downregulated N-cadherin and enhanced of vitamin D3 metabolite expression of E-cadherin.